Dynamic DEMATEL Group Decision Approach Based on Intuitionistic Fuzzy Number - Hui Xie; Wanchun Duan; Yonghe Sun; Yuanwei Du (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
With respect to the problems of aggregation about group experts’ information and dynamic decision in DEMATEL(decision making trial and evaluation laboratory), a dynamic DEMATEL group expert decision-making method on intuitionistic fuzzy number(IFN) is presented. Firstly using IFN instead of original point estimates to reflect the experts’ preference, the group experts’ information are integrated horizontally at each period. Then the aggregation information at different periods are aggregated vertically again by dynamic intuitionistic fuzzy weighted averaging (DIFWA) operator so as to obtain the dynamic intuitionistic fuzzy DEMATEL total relation matrix. Thirdly, through the analysis of center and reason degree, the positions of the various factors in the system are clear and definite, and the inner structure of system has been revealed. Finally, the feasibility and practicability of the proposed method is shown through an illustrative example of a process of course selection in a school.